Characterization of a New S8 serine Protease from Marine Sedimentary Photobacterium sp. A5–7 and the Function of Its Protease-Associated Domain - Li, Hui-Juan; Tang, Bai-Lu; Shao, Xuan; Liu, Bai-Xue; Zheng, Xiao-Yu; Han, Xiao-Xu; Li, Ping-Yi; Zhang, Xi-Ying; Song, Xiao-Yan; Chen, Xiu-Lan (Frontiers in Microbiology, 2016)
Bacterial extracellular proteases are important for bacterial nutrition and marine sedimentary organic nitrogen degradation. However, only a few proteases from marine sedimentary bacteria have been characterized. Some subtilases have a protease-associated (PA) domain inserted in the catalytic domain. Although structural analysis and deletion mutation suggests that the PA domain in subtilases is involved in substrate binding, direct evidence to support this function is still absent. Here, a protease, P57, secreted by Photobacterium sp. A5-7 isolated from marine sediment was characterized. P57 could hydrolyze casein, gelatin and collagen. It showed the highest activity at 40°C and pH 8.0. P57 is a new subtilase, with 63% sequence identity to the closest characterized protease. Mature P57 contains a catalytic domain and an inserted PA domain. The recombinant PA domain from P57 was shown to have collagen-binding ability, and Phe349 and Tyr432 were revealed to be key residues for collagen binding in the PA domain. This study first shows direct evidence that the PA domain of a subtilase can bind substrate, which provides a better understanding of the function of the PA domain of subtilases and bacterial extracellular proteases from marine sediment.